식량안보문제의 발생가능성과 대비방안 - 김명환 (한국농촌경제연구원, 2008)
Food security exists when all people, at all times, have physical and economic access to sufficient, safe and nutritious food. To achieve national food security, a country must be able to grow sufficient food, to have enough foreign exchange to enable it to import food, and to have sufficient buffer stocks. Food crisis in 1973 was mainly caused by the shortage of wheat production of former Soviet, and it took a decade to recover. The recent sharp price increase of 2007/2008 is mainly caused by the demand shift for feed grain in China, ethanol use in US, and increase of speculative demand of international hot money. These demand-pull factors may continue for a decade or longer, grain prices are forecasted to stay high with fluctuations. On the contrary, grain prices may fall if the world economy decrease. Korea experienced several food crisis like the bad crop in 1980, and the foreign exchange crisis in 1997. Countermeasures against such national financial crisis, bad crops, or sudden unification with North Korea are needed. Prices of domestic grain used to be four to five times higher than the import prices. As the international prices went up, the price gap reduced to less than two times. Furthermore, domestic consumers have willingness to pay more for domestic grain. Domestic production of grain is now somewhat competitive. The self-sufficient ratio of grain decreased to 27.2 percent in 2007. Plantation of wheat, barley and green manure crop after the harvest of rice in the winter season may increase the self-sufficient ratio up to 30 percent. Demand for the land for urban and industrial use is projected to be 385,000 hectare up to 2020. The supply capacity of land except the arable land is 678,000 hectare which exceed the demand. In buying and selling of public stockholding of rice, the government may operate a formula to minimize the probability of shortage as well as overstock. And the public stockholdings for wheat, corn and soybean are needed. Private trade companies or National Agricultural Cooperatives Federation are encouraged to enter into the international grain trade in spot market and futures market. Premium rice may be exported to US, Japan and China market in the future. Uruguay Round Agreement for agriculture is generous for export ban, while it is very strict for import ban. It should be discussed in the World Trade Organization. Researchers: Myung-Hwan Kim, Tae-Gon Kim, Soo-Suk Kim Research period: Dec. 2007 - Aug. 2008 E-mail: kimkim@krei.re.kr